An Overview of the Prospects of Bio-fertilizers in Indian Farming (International Journal of Innovative Research in Engineering & Management, 2023)
Only importation and subsidies has  ensured that fossil fuel-based chemical fertilisers are  available and affordable at the agricultural level in India.  Biofertilizers have developed as a highly potent alternate to chemical fertilisers because to their enviromentally,  easy-to-apply, pro, and expense properties. They also act  as a supplement to agrochemicals by allowing plants to  access micronutrients that are naturally abundant in soil or  the ecosystem. Furthermore, if adequate information is  made available to farmers and producers via experiences  and communication, they have the possibility to be  commercially sustainable in the long term. The  government of India is aiming to increase the usage of bio  fertilisers in combination with modern agrochemical. This  paper emphasises the importance of high productivity and  increased and active engagement in science and  technology, public awareness programmed to increase the  extra possibilities of sustainable agricultural extension, and  encouraging private organisations and decision makers to  consider taking a passion for science in the Indian context  and for its coming years in India, as well as trying to  encourage private organisations and decision makers to  take an interest in this topic in the Indian context including  its future in India.
Keywords: Bacteria; Biofertilizers; Nitrogen; Phosphorous; Rhizobium